Pengaruh Pembiayaan Syariah, Rata-Rata Lama Sekolah dan PDRB di Pulau Sumatera 2015-2024 - Nadya Nafisha; Haikal Rahman; Eko Wahyu Nugrahadi; Dita Eka Pertiwi Sirait; Zulkarnain Siregar (Forum Kerjasama Pendidikan Tinggi, 2026)
Economic inequality in Sumatra remains an important issue in regional development, as reflected in disparities in income distribution across provinces. This inequality is presumed to be influenced by various factors, including access to financing, education levels, and regional economic performance. This study aims to analyze the effect of Islamic financing, average years of schooling, and Gross Regional Domestic Product (GRDP) per capita on economic inequality across 10 provinces in Sumatra during the period 2015–2024. The research employs a quantitative approach using panel data regression with the Common Effect Model, and data processing is conducted using EViews software to examine the relationships among variables. The results indicate that Islamic financing, average years of schooling, and GRDP per capita do not have a significant effect on economic inequality, either partially or simultaneously. The coefficient of determination of 2.33% suggests that the variables in the model explain only a small portion of the variation in economic inequality, while the remaining 97.67% is influenced by other factors outside the model. These findings imply that reducing economic inequality in Sumatra requires a more comprehensive approach by incorporating additional relevant variables.